In the shadow of minority rights : decolonising gender, liberalism and the politics of difference / Sagnik Dutta. - Dutta, Sagnik (Cambridge University Press, 2025)
How and where do religious minorities claim their rights? This book challenges abstract liberal approaches to minority rights and colonial constructions of the minority. It charts a new way of understanding minority rights based on an exploration of the everyday life of Muslim women's activism in Mumbai and its intersection with transnational feminist networks and a global politics of Islamic reform. It shows how women deploy everyday ideas of ethics and bodily practices to challenge inequality in Muslim family law. They construct a just community based upon the ethical ideals of the Quran and rights guaranteed by the Indian Constitution and negotiate for rights within homes, police stations, and neighbourhoods in ghettoes. Everyday familiarity is interlaced with violence in women's interactions with the state and non-state actors as they claim their rights, and practices of ethics and intimate negotiations with processes of ghettoisation and violence shape the everyday life of rights.